(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
This paper documents an online discussion conducted during the COVID-19 pandemic. In the course of this, the authors note that psychotherapy teaching is extremely under-documented, under-researched and under-evaluated, and they formulate some preliminary ideas about how existential therapy can be taught in a way that is congruent with the ethos of existential philosophy with the aim of encouraging further work on this important area.